CdO-Ag-ZnO nanocomposites with hierarchically porous structure for effective VOCs gas-sensing properties. Issue 4 (March 2019) - Xing, Xinxin; Yang, Yue; Yan, Zhiyong; Hu, Ying; Zou, Tong; Wang, Zidong; Wang, Yude
Abstract: In this work, CdO-Ag-ZnO nanocomposites with hierarchically porous structure and large surface area were successfully fabricated by solution combustion synthesis (SCS) method. Crystalline structure, morphology, surface chemical states and specific surface area were investigated by XRD, SEM, TEM, XPS and BET techniques, respectively. Sensors fabricated from CdO-Ag-ZnO nanocomposites were made based on indirect heating method, which showed superior sensing properties in detecting different concentration of volatile organic compounds (VOCs). In contrast with singular ZnO, gas-sensing experiment results reveal that the addition of CdO and Ag effectively decreases optimum working temperature, increases gas response value and shortens response and recovery time. What's more, other gas-sensing properties including repeatability, sensitivity and long-term stability are also discussed in this research. Particularly, gas sensor based on 10 mol% CdO-Ag-ZnO shows modest gas-sensing performance to VOCs at the operating temperature of 200 °C, and its gas response values are 198.63, 156.07, 53.04, 64.23, 183.65 towards 100 ppm formaldehyde, ethanol, acetone, methanol and isopropanol, respectively, indicating it a promising candidate in detecting VOCs. Superior sensing property is mainly ascribed to large specific surface area, special porous surface morphology, unique combination of nanocomposites and good catalytic ability of metallic Ag.